Value sharing strategy of digital empowerment high-quality commercialization of agricultural products - Zhan, Shuai; Jin, Shanshan (Frontiers in Sustainable Food Systems, 2024)
This study considers the digital input of multiple subjects, builds a value-added sharing model of the high-quality commercialized value of digitally empowered agricultural products, and uses the Shapley value method to explore reasonable conditions for value-added sharing based on identifying the value-added value of multiple subjects after high-quality commercialization of digitally empowered agricultural products. The three main interests of the study are farmers, logistics companies, and retail enterprises. The findings indicate that various entities involved in the superior commercialization of agricultural products enabled by digital technology will partake in the valueadded benefit of such commercialization, and the extent of digital investment made by these entities and the outcomes of their superior commercialization will determine how value-added sharing is differentiated. Farmers and logistics companies are more willing to participate in digitalization when the cost difference that retail companies pay them exceeds the cost change of their digital enabling high-quality commercialization and a reasonable amount of value-added value is obtained. This helps to form a logically closed loop of "digital empowerment -quality enhancing -value increasing" of value-added sharing. To achieve the high-quality commercialization of agricultural products based on the principle of acceptable value value-added sharing, various subjects should develop a fair value value-added sharing plan that takes into account the varying degrees of digital investment and price variations.